2024
DOI: 10.1542/peds.2023-063667
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Genomic, and Immunological Characterization of RSV Surge in Sydney, Australia, 2022

Gregory J. Walker,
Charles S.P. Foster,
Andrea Sevendal
et al.

Abstract: OBJECTIVES: The 2022 seasonal respiratory syncytial virus (RSV) epidemic in Sydney, Australia saw an unprecedented number of RSV detections. We aimed to characterize genomic and immunologic factors associated with the surge in RSV cases. METHODS: Whole genome sequences of RSV were generated from 264 RSV-infected infants and linked to case-matched clinical data from the 2022 southern hemisphere RSV season. We then performed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In 2022, the number of RSV cases in the state of New South Wales was about four times higher than in 2021. Similarly, large seasonal outbreaks of RSV were accompanied by increased hospitalizations in the northern hemisphere during the same period [16].…”
Section: Rsv Seasonalitymentioning
confidence: 94%
“…In 2022, the number of RSV cases in the state of New South Wales was about four times higher than in 2021. Similarly, large seasonal outbreaks of RSV were accompanied by increased hospitalizations in the northern hemisphere during the same period [16].…”
Section: Rsv Seasonalitymentioning
confidence: 94%
“…One significant advanatage of this drug over palizumab is that it requires only one shot, rather than five monthly shots for palizumab, which greatly reduces the cost. It has recently been approved by the U.S. Food and Drug Administration (FDA) [36].…”
Section: Nirsevimabmentioning
confidence: 99%
“…However, increased age has not been mechanistically tied to an immunity debt, and was also observed among children diagnosed in 2020 14 , the year in which the debt was supposedly accumulating. While two studies have identified a decline in RSV-targeting IgG concentrations during the pandemic 15,16 , another study found no change in neutralizing antibody titers, 17 such that the clinical or epidemiological relevance of this decline is unclear. The alternative “immunity theft” hypothesis posits that COVID-19 infections weakened our immune response to other pathogens.…”
Section: Introductionmentioning
confidence: 97%